Advances in the discovery and development of heat-shock protein 90 inhibitors for cancer treatment - Patel, Hardik J (2011)
INTRODUCTION: Over the last 15 – 20 years, targeted anticancer strategies have focused on therapies aimed at abrogating a single malignant protein. Agents that are directed towards the inhibition of a single oncoprotein have resulted in a number of useful drugs in the treatment of cancers (i.e., Gleevec, BCR-ABL; Tarceva and Iressa, EGFR). However, such a strategy relies on the notion that a cancer cell is dependent on a single signaling pathway for its survival. The possibility that a cancer cell may mutate or switch its dependence to another signaling pathway can result in the ineffectiveness of such agents. Recent advances in the biology of heat-shock protein 90 (Hsp90) have revealed intimate details into the complexity of the chaperoning process that Hsp90 is engaged in and, at the same time, have offered those involved in drug discovery several unique ways to interfere in this process. AREAS COVERED: This review provides the current understanding of the chaperone cycle of Hsp90 and presents the multifaceted approaches used by researchers in the discovery of potential Hsp90 drugs. It discusses the phenotypic outcomes in cancer cells on Hsp90 inhibition by these several approaches and also addresses several distinctions observed among direct Hsp90 ATP-pocket competitors providing commentary on the potential biological outcomes as well as the clinical relevance of such features. EXPERT OPINION: The significantly different phenotypic outcomes observed from Hsp90 inhibition by the many inhibitors developed suggest that the clinical development of Hsp90 inhibitors would be better served by careful consideration of the pharmacokinetic/pharmacodynamic properties of individual candidates rather than a generic approach directed towards the target.